Early age at menarche and history of sexually transmitted infections significantly predict cervical cancer screening uptake among women aged 25-49 years: evidence from the 2021 Côte d'Ivoire demographic and health survey - Joshua Okyere; Castro Ayebeng; Kwamena Sekyi Dickson (BMC, 2024)
Abstract Introduction Cervical cancer is the second dominant type of cancer among Ivorian women with an estimated age-standardised incidence and mortality rate of 31.2 cases and 22.8 deaths per 100,000 women in 2020, respectively. The Ivorian government through its Ministry of Health implemented the National Cancer Control Programme (NCCP) in 2003 with the aim of improving the prevention, early detection and treatment of cancers in Côte d'Ivoire. Yet, there is a low uptake of CCS (1.2%). Thus, making CCS uptake an important public health concern in the country. Understanding of the extent to which reproductive factors predict CCS uptake is limited in literature. This study aimed to investigate reproductive factors as a predictor of women's uptake of CCS in Côte d'Ivoire. Methods Data from the 2021 Côte d'Ivoire Demographic and Health Survey. A sample of 9,078 women aged 25-49 years were analyzed. The outcome variable was CCS uptake while other variables considered included age at menarche, history of STI, sexual debut, parity, age, educational level, wealth index, health insurance, place of residence, and media exposure. A multivariable logistic regression model was fitted to examine the association between the outcome of interest and predictors at 95% confidence interval. Results Approximately, 7.52% of women aged 25-49 years had ever undergone testing for cervical cancer by a healthcare provider. Early menarche was associated with lower odds of CCS uptake [AOR = 0.78; CI = 0.65-0.95]. Compared to those who had no STI, women with a history of STI were more likely to screen for cervical cancer [AOR = 2.63; CI = 2.02-3.42]. Increasing age, higher educational attainment, having health insurance, and being exposed to media were significantly associated with CCS uptake. Conclusion In Cote d'Ivoire, age at menarche and STI history constitute reproductive factors that were significantly associated with women's uptake of CCS. It is imperative for public policy to focus on increasing CCS in these higher-risk women (i.e., women who experienced early menarche, women with early sexual debut and higher parity) through increased sensitization on cervical cancer risk factors.